Research and application of flight trajectory data compression algorithm - YANG Yao, XIAO Yajuan (Zhihui kongzhi yu fangzhen)
The vast amount of flight trajectory data brings huge challenges to the data storage, data query, and data visualization in the situational display system, and data compression technology is an effective solution to this problem. Regarding the problems that the current flight trajectory compression algorithms do not effectively utilize all flight parameter features and need to set thresholds manually, this paper proposes an effective flight trajectory data compression algorithm. The algorithm first performs clustering on the flight direction parameters and selects trajectory feature points based on the category labels. Then, the algorithm calculates the information entropy to determine the score of each trajectory feature point, and compresses the trajectory data based on the compression rate and score sorting. The simulation results show that compared with other algorithms, the proposed algorithm has better compression quality and compression efficiency. By applying the algorithm to the trajectory playback and trajectory envelope visualization in the situational display system, the system response speed and display efficiency can be significantly improved.